The campaign of brushing teeth before going to bed to prevent dental caries in "Pesantren Dayah Insan Qurani" students in Aceh Besar - Irmi Fitria (BKM Public Health and Community Medicine, 2021)
Dental and oral health is very important. The incidence of dental and oral disease in Indonesia, especially Aceh, is still relatively high. Riskesdas data (2018) noted that the proportion of dental and oral problems was 57.6%, and those who received services from dental personnel were 10.2%. The proportion of correct tooth brushing behavior is 2.8%. The high number is inseparable from the low behavior of good oral hygiene in individuals and communities. Promotive and preventive programs as an initial step to prevent dental and oral diseases are still often neglected. Santri in pesantren is also inseparable from this problem so that it is not uncommon for many students to experience a toothache. Students in boarding schools understand that cleanliness is part of faith. However, there are times when they neglect to perform oral hygiene properly, and the lack of information is obtained so that the condition of their teeth and mouth often becomes problematic. Promotive and preventive programs through brushing teeth before bed are the first step in preventing dental caries and periodontal disease. Caries can occur due to several factors, namely dental plaque, host (teeth), food (substrate)and, and time. The four components are interconnected so that doing the right toothbrush (action oral hygiene) is an action to break the chain of these four components. The students are encouraged to brush their teeth twice a day (morning after breakfast and night before going to bed). The hope can be optimistic in maintaining the health of their oral cavity. This action was carried out with the full supervision of the hostel caregivers as the person in charge (parents) of fostering students at the boarding school. The dormitory caretaker is the closest person to the students and protects them so that their orders will be easily heard and followed by the students. In addition, the dormitory caregivers are also substituting parents so that they are more aware of the ins and outs of the health problems experienced by students. This program has been well designed by the dentist at the pesantren clinic. In addition, this program is approved by the director of the boarding school's health. The pesantren leadership is also involved in enforcing this program as the main person in charge. Students' activities start from waking up before dawn and at night after reading the Koran. In the evening, the santri activities will be closed by reading the Qur'an together in their respective dormitories. The program of brushing teeth before bed is carried out simultaneously with the students taking ablution and reading the Qur'an together. Before going to bed, all the students had gathered in their respective dormitories with a total of 18-24 students. The gathering of the students made it easy for the caregivers to coordinate so that this tooth brushing activity would be easy to carry out. Before this activity begins, the dentist will first provide socialization to each dormitory. Caregivers have full responsibility for these activities. Dentists monitor the team's performance. Each day will be made a list checklist to monitor anyone who commits a toothbrush at night. If dormitories have not carried out this activity thoroughly, evaluation and re-socialization will be carried out periodically. Then, students in dormitories who brush their teeth regularly before going to bed will be named the best dormitory and get a reward as a form of appreciation. Kesehatan gigi dan mulut merupakan hal yang sangat penting. Angka kejadian penyakit gigi dan mulut di Indonesia khususnya Aceh masih tergolong tinggi. Data Riskesdas (2018) mencatat proporsi masalah gigi dan mulut sebesar 57,6% dan yang mendapatkan pelayanan dari tenaga medis gigi sebesar 10,2%. Adapun proporsi perilaku menyikat gigi dengan benar sebesar 2,8%. Tingginya angka tersebut tidak terlepas dari rendahnya perilaku oral hygiene yang baik pada individu maupun komunitas. Program promotif dan preventif sebagai langkah inisial mencegah terjadinya penyakit gigi dan mulut masih sering diabaikan. Santri di pesantren juga tidak terlepas dari permasalahan ini sehingga tidak jarang banyak santri yang mengalami sakit gigi. Santri yang tinggal di pesantren tentunya mengerti bahwa kebersihan sebagian daripada iman. Namun, ada kalanya mereka abai untuk melakukan oral hygiene secara benar dan kurangnya informasi yang didapatkan sehingga kondisi gigi dan mulutnya menjadi sering bermasalah. Program promotif dan preventif melalui menyikat gigi sebelum tidur merupakan langkah awal dalam mencegah terjadinya karies gigi dan penyakit periodontal. Karies dapat terjadi karena beberapa faktor yaitu plak gigi, host (gigi), makanan (substrat) dan waktu. Keempat komponen tersebut saling berhubungan sehingga melakukan sikat gigi (tindakan oral hygiene) yang tepat merupakan tindakan untuk memutus mata rantai keempat komponen tersebut. Para santri dianjurkan untuk melakukan sikat gigi dua kali sehari (pagi setelah sarapan dan malam sebelum tidur). Harapannya dapat bernilai positif dalam memeliharan kesehatan rongga mulut mereka. Aksi ini dilakukan dengan pengawasan penuh dari pengasuh asrama sebagai penanggungjawab (orangtua) asuh santri di pesantren. Pengasuh asrama merupakan sosok yang paling dekat dengan santri dan yang mengayomi mereka sehingga perintahnya akan mudah didengar dan diikuti oleh santri. Selain itu, pengasuh asrama juga merupakan orangtua pengganti sehingga lebih mengetahui seluk beluk permasalahan kesehatan yang dialami oleh santri. Program ini sudah dirancang dengan baik oleh dokter gigi klinik pesantren. Selain itu program ini disetujui oleh direktur kesehatan pesantren. Pimpinan pesantren juga ikut terlibat dalam menegakkan program ini sebagai penanggungjawab utama. Kegiatan santri dimulai dari bangun tidur sebelum subuh dan malam setelah mengaji. Pada malam hari kegitatan santri akan ditutup dengan membaca al-Qur’an bersama di asrama masing-masing. Program menyikat gigi sebelum tidur ini dilakukan bersamaan dengan para santri mengambil wudhu dan melakukan baca al-Qur’an bersama tersebut. Sebelum tidur seluruh santri sudah berkumpul di asrama masing-masing dengan jumlah santri sekitar 18-24 orang. Berkumpulnya para santri ini menjadi mudah bagi pengasuh untuk melakukan koordinasi sehingga kegiatan menyikat gigi ini akan mudah dilaksanakan. Sebelum aski ini dimulai, terlebih dahulu dokter gigi akan memberikan sosialisasi ke tiap-tiap asrama. Tindakan ini juga diberikan tanggungjawab penuh kepada pengasuh dan dokter gigi berperan sebagai tim pemantau untuk melihat progress program ini. Setiap harinya akan dibuat daftar check list untuk memantau siapa saja yang melakukan sikat gigi pada malam hari. Apabila ada asrama yang masih belum melakukan kegiatan ini secara menyeluruh maka akan dilakukan evaluasi dan sosialisasi ulang secara berkala. Kemudian, untuk asrama yang melakukan kegiatan menyikat gigi secara teratur sebelum tidur akan dinobatkan sebagai asrama terbaik dan mendapatkan reward sebagai bentuk apresiasi.